2017
DOI: 10.1071/ma17042
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia pecorum: successful pathogen of koalas or Australian livestock?

Abstract: In Australia, the obligate intracellular bacterium Chlamydia pecorum is best known as the notorious koala pathogen that causes debilitating ocular and urogenital tract disease.While globally published data suggests that this species is essentially ubiquitous in livestock, little is known about the epidemiology of livestock C. pecorum infections here in Australia. My research is focused on investigating the genetic diversity and transmission patterns of C. pecorum, and why it causes disease. Using our newly dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…34 MLST has demonstrated that multiple genetically distinct C. pecorum genotypes are present in both healthy and diseased sheep and cattle, sometimes varying by anatomical site. 15,17,18 The genotype of C. pecorum found in all 3 fetuses was determined to be ST23, which has been previously associated with multiple disease states in different hosts, including ovine polyarthritis and conjunctivitis, and sporadic bovine encephalomyelitis in cattle in Western Australia, the United States, and England. [15][16][17][18]39 Although not pathognomonic, gross placental lesions were consistent with findings in experimental ovine C. pecorum abortion following intravenous inoculation, 30 and gross and histologic findings with natural caprine C. pecorum abortion.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…34 MLST has demonstrated that multiple genetically distinct C. pecorum genotypes are present in both healthy and diseased sheep and cattle, sometimes varying by anatomical site. 15,17,18 The genotype of C. pecorum found in all 3 fetuses was determined to be ST23, which has been previously associated with multiple disease states in different hosts, including ovine polyarthritis and conjunctivitis, and sporadic bovine encephalomyelitis in cattle in Western Australia, the United States, and England. [15][16][17][18]39 Although not pathognomonic, gross placental lesions were consistent with findings in experimental ovine C. pecorum abortion following intravenous inoculation, 30 and gross and histologic findings with natural caprine C. pecorum abortion.…”
Section: Discussionmentioning
confidence: 99%
“…MLST has demonstrated that multiple genetically distinct C. pecorum genotypes are present in both healthy and diseased sheep and cattle, sometimes varying by anatomical site. 15,17,18 The genotype of C. pecorum found in all 3 fetuses was determined to be ST23, which has been previously associated with multiple disease states in different hosts, including ovine polyarthritis and conjunctivitis, and sporadic bovine encephalomyelitis in cattle in Western Australia, the United States, and England. 15 18,39…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations